Preoperative and Operative Risk Factors Associated with the Conversion of Laparoscopic Cholecystectomy to Open Surgery - Kamran Hyder Abbasi; Irshad Ahmed; Shah Nawaz Khatti; Anam Shah; Mujahid ur Rehman; Imam Alam, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Although laparoscopic cholecystectomy (LC) is the standard treatment for gallbladder disease, some cases still require conversion to open cholecystectomy (OC). Identifying risk factors for conversion can improve surgical outcomes and decision-making. Study Design: A prospective study Duration and place of study: This study was conducted in Liaquat University of Medical and Health Sciences Jamshoro Pakistan from December 2023 to December 2024 Methods:A prospective study was conducted, involving 200 patients who underwent LC. Patients were grouped based on whether conversion to OC occurred. Clinical and operative factors were analyzed using SPSS v26.0, with p<0.05 considered statistically significant. Results : The conversion rate was 7.78%. Significant risk factors included age ≥65, obesity, diabetes, and prior abdominal surgery. Elevated ALP, bilirubin, dilated CBD, and multiple gallstones on ultrasound were also associated with higher conversion risk. Intraoperative findings such as dense adhesions, empyema, perforated, and scleroatrophic gallbladder were linked to conversion. Preoperative ERCP showed no significant association. Conclusion:While LC remains the preferred approach, OC is a necessary and safe option in complex cases. Recognizing risk factors early can help anticipate the need for conversion and guide operative planning.